Translation, cross-cultural adaptation and validation of User Mobile App Rating Scale (uMARS) - Tuan Soh, Tuan Yuswana; Nik Mohd Rosdy, Nik Mohd Mazuan; Md Sabri, Budi Aslinie (IIUM Journal of Orofacial and Health Sciences, 2025)
The user Version Mobile apps rating scale was established to evaluate the mobile apps. However, to date, there is no uMARS in the Malay version. This study aims to develop a Malay language alternative to the existing version of the Mobile Apps Rating Scale. The initial version of uMARS had previously underwent cross-cultural adaptation, and forward-backward translation with synthesis discussion through a development phase. The upgraded Malay version has been screened and rated by 10 respondents for face validation and a total of 36 respondents contributed to the internal reliability assessment by answering the pilot study question. All items and constructs in the uMARS version were fully adapted. All items and constructs from the prior version of uMARS were fully incorporated into the recent version. The Malay language version of uMARS was subsequently assessed for validity as well as reliability after undergoing forward backward translation. Scale level face validity index based on average method (S-FVI/Ave): 0.99, and S-FVI based on universal agreement method (S-FVI/UA): 0.89 showed that uMARS Malay Version has achieved a satisfactory level of response process validity. Whereas all items and construct presented with excellent internal reliability, Cronbach alpha (?) = 0.918, 0.857, 0.984 for objective quality, subjective quality and perceived impact. The Malay language of uMARS represents the outcome produced through proper development and validation of questionnaires; all of which favourably resulted in an updated version of uMARS that has been deemed competent to be utilized for qualitative measurement of mobile health apps in the Malay language.